Improving Pkn Learning Outcomes With The Application Of The Pakem Method In Class VI.b State Elementary School 003 Created For The 2019/2020 Academic Year - Robina Simanjuntak (Indonesian Journal of Basic Education, 2021)
Classroom Action Research conducted at SDN 003 Rambah in the VIB class aims to improve the learning outcomes of Civics. This research was conducted in T.P 2019/2020. Conditions in the initial study before using the PAKEM method of students who reached the criteria for mastery learning only 9 students out of 25 students. After using the PAKEM method in the first cycle students who reached KKM became 25 students from 25 students, improvement in cycle II students who reached KKM became 19 students from 25 students. Improvement of cycle III students who reached KKM became 23 students from 18 students. The application of the PAKEM method can train students' independence in solving a problem, so that the teacher is not used as a center of learning but the teacher is only a facilitator